2013
DOI: 10.1371/journal.pone.0066212
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Scholarly Authorship

Abstract: Gender disparities appear to be decreasing in academia according to a number of metrics, such as grant funding, hiring, acceptance at scholarly journals, and productivity, and it might be tempting to think that gender inequity will soon be a problem of the past. However, a large-scale analysis based on over eight million papers across the natural sciences, social sciences, and humanities reveals a number of understated and persistent ways in which gender inequities remain. For instance, even where raw publicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
609
3
22

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 699 publications
(710 citation statements)
references
References 27 publications
40
609
3
22
Order By: Relevance
“…PAID also reflects this trend, and the average number of authorships/article increased from (West et al, 2013). In other fields, such as mathematics or economics, the author order is usually alphabetical (Waltman, 2012;West et al, 2103).…”
Section: Pattern Of Collaborationmentioning
confidence: 93%
See 1 more Smart Citation
“…PAID also reflects this trend, and the average number of authorships/article increased from (West et al, 2013). In other fields, such as mathematics or economics, the author order is usually alphabetical (Waltman, 2012;West et al, 2103).…”
Section: Pattern Of Collaborationmentioning
confidence: 93%
“…Despite significant progress in recent years, bibliometric analyses of the worldwide research production show that gender imbalances persist, and women are still underrepresented in most scientific fields (less than 30% of authorships worldwide; see Larivière, Ni, Gingras, Cronin, & Sugimoto 2013;West, Jacquet, King, Correll, & Bergstrom, 2013). Bibliometric studies in psychology are abundant, but gender analyses are scarce and not recent enough (Boice, Shaughnessy, & Pecker, 1985;Guyer & Fidell 1973), or limited to a specific geographical area, such as Australia (Malouff, Schutte, & Priest, 2010), Italy (D'Amico, Vermigli, & Canetto, 2011), or Spain (Barrios, Villarroya, & Borrego, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within scholarly publishing, a field with close ties to academic and scholarly communications librarianship, a 2014 analysis of the Society of Scholarly Publishers (SSP) members found that 58% were women (Kane & Meadows, 2014). As an analysis by West, Jacquet, King, Correll, and Bergstrom (2013) found, however, even in academic fields where genders were relatively evenly distributed, gender distribution within subfields can vary widely. It is therefore unclear which trends, if any, are applicable to scholarly communications librarianship, which has yet to be singled out for analysis.…”
Section: Literature Review Gender Distribution In Lis and Scholarly Cmentioning
confidence: 99%
“…It may also be that men continue to be more visible and hence more likely to be identified as 164" potential board members because they have greater productivity, have more first-or last-authors 165" of papers (West et al 2013), and tend to be "citation elites" (sensu Parker, Allesina & Lortie 166" 2013;Parker, Lortie & Allesina 2010). It may be that using these metrics to screen for editors 167" might eventually -albeit slowly -result in increased numbers of women on editorial boards.…”
mentioning
confidence: 99%
“…This is because gender-based disparities in rates of publication (West et al 2013) and citation 169" (Borsuk et al 2009) are diminishing (but see Lariviere et al 2013), although this does not appear 170"…”
mentioning
confidence: 99%